Implementation of an action plan to improve the English Language learning process of the 7th A grade students of the Colegio Bilingüe de Panama = Implementación de un plan de acción para mejorar el proceso de aprendizaje del idioma inglés de los alumnos de 7 ° grado del Colegio Bilingüe de Panamá - Sanjur Rodríguez, Arquímedes; De León, Rodrigo Ernesto (Panamá, Panamá : UDELAS, 2019)
To explore the factors that affect the process of learning English as a second language and try solutions to reduce the issue and to adopt an action plan to increase the desire of studentss to learn this essential language at the Escuela Bilingue de Panamá. Español: Explorar los factores que afectan el proceso de aprendizaje del inglés como segundo idioma y probar soluciones para reducir el problema y adoptar un plan de acción para aumentar el deseo de los estudiantes de aprender este idioma esencial en la Escuela Bilingüe de Panamá.
TABLE OF CONTENT INTRODUCCIÓN CHAPPER I: THEORETICAL FRAMEWORK OF THE PROJECT CHAPTER II: THEORETICAL FOUNDATION CAPTER III: ANALYSIS AND INTERPRETATION OF RESULTS CONCLUSION RECOMENDATIONS BIBLIOGRAPHYC REFERENCES APPENDIX INSTRUMENTS APPLIED IN THE PROYECT ASSESSMENT TO ACTIVITIES APPLIED
Presentada para optar al Título de Maestría en Licenciatura en Enseñanza del Idioma Inglés
Incluye Bibliografía
Solo para uso en sala.
No se debe fotocopiar.
Keywords: IDIOMA INGLÉS - ENSEÑANZA -- PROYECTO -- ESCUELA DE PEDAGOGÍA; COLEGIO BILINGÜE DE PANAMÁ